The Reasons For Refraining from the Most Correct Saying to other Sayings and Some of the Implications - Hussein , Mustafa (Islamic Sciences Journal, 2023)
One of the requirements of Salah Islamic law is renewal in ijtihad, which is necessary in the equation of the changing life in its elements place, time, custom, and conditions. It is not from the justice and mercy of the law, nor from the requirements of its permanence to continues in indging people in the same wey of treating those who preceded them for several centuries, it is an issne that contradicts its grace and validity. The Islamic jurisprudence is the jurisprudence of high-end human life, and It is the jurisprudence of growth, development and flexibility that are appropriate to the condition of Muslims,their strength and weakness, and in various areas of life. Ijtihad, including selective ijtihad, which is concerned with choosing the most appropriate juristic statement of the descending, and attached to people, and the closest to the purposes of Sharia among other jurisprudential sayings, Therefore the scholars stipulated to carry out this type of ijtihad, and selection which include a set of conditions it, and should be surrounded by a set of controls Otherwise the selection will be according to whims and arbitration of the purposes; which made scholars refrain from the most correct saying to other sayings, so that the matter would not be a cause for self-interest.